PERAN PENDAMPINGAN REGULASI EMOSI TERHADAP PERILAKU MALTREATMENT PADA IBU DARI ANAK GPP/H - Erny Hidayati (HUMANITAS: Indonesian Psychological Journal, 2013)
AbstractThis study was aimed to examine the role of emotion regulationassistance to decrease of physical maltreatment behavior, namely pinching behavior on mothers of ADHD children. This research was used within subject design with ABAB single subject design. There were two mothers of ADHD children participating in this study. They were clients of The Assessment Center for Child Growth and Development in Yogyakarta. Data were obtained from self monitoring note and reflection of experience during emotion regulation assistance study period was going on. Datawere analyzed by using visual inspection. Data of subject reflection during assistance period were analyzed qualitatively using content analysis approach. The result showed that emotion regulation assistance evoked the change of awareness on both subjects. The new awareness influenced the way of the subjects to view behavior of ADHD children. Furthermore this influenced on decreasing physical maltreatment behavior, namely pinching behavior monitored.Keyword: ADHD, physical maltreatment, regulation emotion assistance